KAJIAN STRATEGI IMPLEMENTASI PROGRAM AGROPOLITAN DI KAWASAN AGROPOLITAN KABUPATEN KAPUAS - , Eddy Koestanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
One of alternatives in regional development is agropolitan model. However, implementation the program were failed in some area. One strategy in this model is commodities change. This research aims to: (1) analyze the strategy change of commodities in the process of implementation of the program agropolitan, (2) reviewing the effectiveness of the strategy change of commodities in the process of implementation of the program agropolitan based on output and outcomesnya and (3) analyze the relationship of the link between the variables that influenced him. The research method used was deductive method with a descriptive qualitative and quantitative approach. The location of research are in three villages in the Subdistrict of Basarang by the number of respondents 114 kk being determined in purposive sampling. The research showed that (1) the occurrence of farm communities in determining the independence of the development of commodity market-oriented business (competitive advantage/competitive advantage)